Price and Transaction Volume in the Dutch Housing Market - Erik R. de Wit; Peter Englund; Marc Francke (Tinbergen Institute, 2010)
Housing markets typically exhibit a strong positive correlation between the rate of price increase and the number of houses sold. We document this correlation on high-quality Dutch data for the period 1985-2007, and estimate a VEC-model that allows us to study the mechanism giving rise to the correlation. The data identify the flows of new houses offered for sale as well as the number of houses sold. According to the estimated model, shocks to market fundamentals (the mortgage rate)have an immediate and significant impact on the rate of sale, little impact on the rate of entry of new houses for sale, and a gradual impact on the house prices. This pattern is consistent with a search model where buyers and sellers gradually learn about changes in market conditions.
Keywords: G12; G21; E29; G17; 330; price-volume correlation; time-on-the-market; vector error correction model; Immobilienpreis; Gesamtwirtschaftliches Angebot; Immobilienmarkt; Kausalanalyse; Niederlande